(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concepts of almost τ^(σ_1,σ_2)-continuous functions and weakly τ^(σ_1,σ_2)-continuous functions. Moreover, some characterizations of almost τ^(σ_1,σ_2)-continuous functions and weakly τ^(σ_1,σ_2)-continuous functions are investigated. Furthermore, the relationships between almost τ^(σ_1,σ_2)-continuity and weakly τ^(σ_1,σ_2)-continuity are considered.